2017
DOI: 10.1038/s41598-017-15176-0
|View full text |Cite|
|
Sign up to set email alerts
|

Determination of total and unbound docetaxel in plasma by ultrafiltration and UPLC-MS/MS: application to pharmacokinetic studies

Abstract: A sensitive and specific liquid chromatographic/tandem mass spectrometric (LC-MS/MS) method was developed and validated for quantifying total and unbound docetaxel drug concentrations in plasma. Calibration curves for unbound and total docetaxel were linear over the respective ranges of 0.108~10.8 and 0.54~216 ng/mL. The intra- and interday assay accuracy and precision did not exceed 15%. The methods were validated to show the standard range linearity, sensitivity, selectivity, accuracy, precision, and stabili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…Validated methods to quantify unbound docetaxel have been reported previously; however, the lowest level of quantification was 0.1-0.4 ng/mL [16,17]. Here, we report the successful development of a slightly more sensitive assay to quantify unbound docetaxel with an LLOQ of 0.084 ng/mL in plasma samples from patients receiving oDox+E.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…Validated methods to quantify unbound docetaxel have been reported previously; however, the lowest level of quantification was 0.1-0.4 ng/mL [16,17]. Here, we report the successful development of a slightly more sensitive assay to quantify unbound docetaxel with an LLOQ of 0.084 ng/mL in plasma samples from patients receiving oDox+E.…”
Section: Discussionmentioning
confidence: 80%
“…Previous assays developed to quantify unbound docetaxel utilised equilibrium dialysis or ultrafiltration to separate the unbound docetaxel followed by HPLC-MS/MS [14][15][16]. These methods report a lower limit of quantification (LLOQ) of 0.1 ng/mL to 0.4 ng/mL [14,16,17]. Given the small starting dose of oDox+E (75 mg/m 2 ), we aimed to develop a more sensitive assay to quantify smaller concentrations of unbound docetaxel.…”
Section: Introductionmentioning
confidence: 99%
“…Along with the plasma DTX concentration illustrated by Figure S3 is the binding activity of HER2-L sb MDDs remained in the plasma at each time point. Since it has been confirmed that after administration of DTX-loaded L sb MDDs, most of DTX in the plasma was encapsulated in L sb MDDs (Sheu et al., 2017 ). Therefore, the binding activity of HER2-L sb MDDs that encapsulated DTX was measured at the same DTX concentration (all were diluted to 5 ng/mL DTX) as an indication of the same HER2-L sb MDDs concentration being loaded in the measurement of the binding activity.…”
Section: Resultsmentioning
confidence: 98%